2014
DOI: 10.3389/fmicb.2014.00168
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine synthetase 2 is not essential for biosynthesis of compatible solutes in Halobacillus halophilus

Abstract: Halobacillus halophilus, a moderately halophilic bacterium isolated from salt marshes, produces various compatible solutes to cope with osmotic stress. Glutamate and glutamine are dominant compatible solutes at mild salinities. Glutamine synthetase activity in cell suspensions of Halobacillus halophilus wild type was shown to be salt dependent and chloride modulated. A possible candidate to catalyze glutamine synthesis is glutamine synthetase A2, whose transcription is stimulated by chloride. To address the ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…In the case of the halophilic archaea H. hamelinensis, salinity levels, and glutamate concentration have been reported to trigger the change of osmotic strategies during the transition from moderate to high salinity. In halophiles generally, the uptake of compatible solutes is performed by multiple porters, such as the symporters and ABC transporters (Falb et al 2008;Saum & Müller 2007;Shiyan et al 2014). Here, we found some symporters like Na + /proline (OpuE), proton/glutamate, sodium/glutamate, and Na + /solute (Becker et al 2014;Edbeib et al 2016;Jung et al, 2012).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…In the case of the halophilic archaea H. hamelinensis, salinity levels, and glutamate concentration have been reported to trigger the change of osmotic strategies during the transition from moderate to high salinity. In halophiles generally, the uptake of compatible solutes is performed by multiple porters, such as the symporters and ABC transporters (Falb et al 2008;Saum & Müller 2007;Shiyan et al 2014). Here, we found some symporters like Na + /proline (OpuE), proton/glutamate, sodium/glutamate, and Na + /solute (Becker et al 2014;Edbeib et al 2016;Jung et al, 2012).…”
Section: Discussionmentioning
confidence: 58%
“…Trehalose can be biosynthesized by the OstAB, TreS, TreP, TreY, and TreT pathways (Avonce et al 2006). Previous studies have also reported that some halophilic cells accumulate glutamate and glutamine in high con-centrations, compatible with osmolytes (Falb et al 2008;Saum & Müller 2007;Shiyan et al 2014). The glutamate could be converted to proline by an alternative pathway in some haloarchaea strains.…”
Section: Discussionmentioning
confidence: 82%